The history of Central Asia - Baumer, Christoph
An illustrated history of one of the most compelling and mysterious regions on earth. It is a unique travelogue and resource and will appeal to scholars and students of antiquity, history, archaeology and religious studies. The epic plains and arid deserts of Central Asia have witnessed some of the greatest migrations, as well as many of the most transformative developments, in the history of civilization. Christoph Baumer's ambitious treatment of the region charts the 3000-year drama of Scythians and Sarmatians; Soviets and transcontinental Silk Roads; trade routes and the transmission of ideas across the steppes; and, the breathless and brutal conquests of Alexander the Great and Chinghiz Khan